HUBUNGAN AKTIVITAS FISIK DENGAN WAIST/HIP RATIO, TEKANAN DARAH, DAN KOLESTEROL PADA MAHASISWA KEDOKTERAN YANG MENGALAMI OVERWEIGHT - Aristo Constantine; Ignatio Rika Haryono (Atma Jaya Catholic University of Indonesia, 2022)
ABSTRACT Introduction: Cardiovascular disease has been a major health problem as of late, with over 17.5 million death per year. Accompanied with many risk factors such as hypercholesterolemia and abnormal body mass index, many researches have sought to find a way to alleviate the number of incidence. Physical activity then has been a well-known way to mitigate such symptoms and though many studies before have given insight on the relationship between physical activity and cardiovascular risk factors, this study aims to determine more closely on the relationship between physical activity in an overweight population with blood cholesterol, blood pressure and waist/hip ratio. Methods: It is a analytic comparative study with a cross-sectional method. The research subjects were 250 people divided into two groups. Physical activity data were obtained using the Global Physical Activity Questionnaire (GPAQ), blood cholesterol level was measured using capillary blood sampling on a easy touch device, blood pressure was measured using a mercury sphygmomanometer, waist/hip ratio was measured using an anthropometric band, body mass index (BMI) was measured by the way the weight divides the body in kilograms (kg) by height in meters squared (m2). Results: Among the overweight students of FKIK UAJ no significant relationship was found between physical activity with blood cholesterol, waist/hip ratio and blood pressure (p > 0.05). Conclusions: There is no significant relationship between physical activity in an overweight population with blood cholesterol, waist/hip ratio, and blood pressure. There is also no significant value differences between physical activity with blood cholesterol, waist/hip ratio, and blood pressure. Keywords: Blood Cholesterol, Blood Pressure, Overweight, Physical Activity, Waist/hip Ratio.